Mortality trends from all causes and diabetes mellitus according to sex between 1998 and 2021 - Negrato Carlos Antonio; Medeiros Gabriel Araújo; Duarte de Souza Giordano Bruno; Lopes Lucas Casagrande Passoni (Open Health, 2024)
The variation of mortality rates according to sex, regarding mortality from all causes and from specific conditions related to diabtes mellitus (DM) is widely discussed.